Assessment of the effectiveness of the fisheries code in fish stock management in the coastal barangays of Davao City - Mebrano, Greta Kuenzle' Gamolo (Davao City UP in Mindanao, 2006)
The objective of this study was to assess the effectiveness of the Fisheries Code in promoting fish stock management in selected coastal barangays of Davao City. Data were gathered through interviews with municipal fishers from Barangay Daliao and Sasa. The study analyzed the level of awareness of the municipal fishers, their level of acceptability and compliance. Results show that policy awareness, acceptability and compliance were high for all both barangays. Fish stock was percieved to be decreasing, especially for Barangay Daliao where they are competing with commercial fishers. Majority of the respondents from both barangays felt the presence of the monitoring groups and percieved them as helpful in improving the quality of the sea. It is recommended that providing alternative livelihood opportunities for the fishers may ease pressure on fishery resource.
Thesis, Undergraduate (BS Economics) -- U.P. in Mindanao, 2006.
Includes bibliographical references.
Keywords: Fishery law and legislation -- Philippines; Fish stocking -- Davao City -- Management